Fatal Tuberculosis in a Free-Ranging African Elephant and One Health Implications of Human Pathogens in Wildlife - Miller, Michele A.; Buss, Peter; Roos, Eduard O.; Hausler, Guy; Dippenaar, Anzaan; Mitchell, Emily; van Schalkwyk, Louis; Robbe-Austerman, Suelee; Waters, W. Ray; Sikar-Gang, Alina; Lyashchenko, Konstantin P.; Parsons, Sven D. C.; et al. (Frontiers in Veterinary Science, 2019)
Tuberculosis (TB) in humans is a global public health concern and the discovery of animal cases of Mycobacterium tuberculosis (Mtb) infection and disease, especially in multi-host settings, also has significant implications for public health, veterinary disease control and conservation endeavours. This paper describes a fatal case of Mtb disease in a free-ranging African elephant (Loxodonta africana) in a high human TB burden region. Necropsy revealed extensive granulomatous pneumonia, from which Mtb was isolated and identified as a member of LAM3/F11 lineage; a common lineage found in humans in South Africa. These findings are contextualized within a framework of emerging Mtb disease in wildlife globally and highlights the importance of the One Health paradigm in addressing this anthroponotic threat to wildlife and the zoonotic implications.